2019
DOI: 10.6028/nist.tn.2033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IF-WS2 nanolubricant on R134a boiling on a reentrant cavity surface:

Abstract: This report quantifies the influence of inorganic fullerene-like tungsten disulfide (IF-WS2) nanoparticles on the pool-boiling performance of R134a/polyolester mixtures on a commercial (Turbo-ESP) boiling surface. Tungsten disulfide nanoparticles, of roughly 150 nm, were used at a 15 % mass fraction in a base polyolester lubricant to produce the test nanolubricant. The nanolubricant was mixed with R134a at a 1 % mass fraction. The study showed that the nanolubricant caused an average 37 % degradation in the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…TN.2125 Considering that R514A is 74.7/25.3 by mass mixture of R1336mzz(Z) and R1130, Fig. 4 compares the present pool-boiling measurements for R514A to the means of the R1336mzz(Z) pool boiling measurements from Kedzierski and Lin (2019) Being that R514A is a replacement for R123, Fig. 4 provides the mean boiling curve for R123 at a saturation temperature of 277.6 K, as taken from and shown as a long-dashed black line.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…TN.2125 Considering that R514A is 74.7/25.3 by mass mixture of R1336mzz(Z) and R1130, Fig. 4 compares the present pool-boiling measurements for R514A to the means of the R1336mzz(Z) pool boiling measurements from Kedzierski and Lin (2019) Being that R514A is a replacement for R123, Fig. 4 provides the mean boiling curve for R123 at a saturation temperature of 277.6 K, as taken from and shown as a long-dashed black line.…”
Section: Resultsmentioning
confidence: 97%
“…They presented an analysis that showed that the nanoparticles were too large and too dense to promote a boiling enhancement. In other work, Kedzierski and Lin (2019) quantified the pool boiling performance of R1336mzz(Z) on the Turbo-ESP surface and showed that the boiling performance of R1336mzz(Z) did not differ statistically from that of R123 for heat fluxes between 13 kWm -2 and 59 kWm -2 . For heat fluxes larger than 59 kWm -2 , the R123 boiling heat flux was up to 5 % larger than the heat flux for R1336mzz(Z).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation